Nutritional value of pearl millet for swine - G L Allee; Gary M Paulsen (Kansas Agricultural Experiment Station Research Reports, 1975)
A growth trial and a digestion trial were conducted using 44 crossbred pigs (initial average weight 40 pounds) to determine the nutritional value of pearl millet as a feedstuff for swine. The millet used contained 11.98% protein (N x 6.25) and 0.40% lysine on a dry matter basis. In the growth trial, replacing 50 or 100% of the corn with millet had no significant effect on feed intake, daily gain, or feed/gain. Results of the digestion trial suggest that the digestibility of protein and energy in millet is similar to that of corn.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Nutrition; Pearl millet; Digestibility